Differentiated expression of long non-coding RNA-small nucleolar RNA host gene 8 in atherosclerosis and its molecular mechanism. Issue 1 (1st January 2021) - Wang, Shuang; Li, Jianchao; Chen, Aimei; Song, He
ABSTRACT: Atherosclerosis (AS) is one of the most common cardiovascular diseases, and the incidence is increasing year by year. Many studies have shown that long non-coding RNA plays a vital role in the pathogenesis of AS. This study aimed to explore the role and mechanism of lncRNA-small nucleolar RNA host gene 8 (SNHG8) in AS. The expressions of serum lncSNHG8 and miR-224-3p were determined by quantitative real-time polymerase chain reaction (qRT-PCR). The diagnostic meaning of lncSNHG8 in AS was estimated by Receiver operating characteristic (ROC) curve. The correlation between lncSNHG8 and various clinical indicators, as well as miR-244-3p was evaluated by Pearson correlation coefficient analysis. Cell proliferation and migration were estimated by cell counting kit-8 (CCK-8) and Transwell assay. The interaction between lncSNHG8 and miR-224-3p was proved by luciferase reporter gene assay. The expression level of lncSNHG8 was increased in AS patients, while miR-224-3p expression was decreased. The ROC curve indicated that lncSNHG8 with high serum expression had the ability to distinguish AS. Pearson correlation coefficient exhibited that the level of miR-224-3p was negatively correlated with the level of lncSNHG8. The results of cell experiments indicated that inhibition of the expression of lncSNHG8 significantly inhibited the proliferation and migration of vascular smooth muscle cells (VSMCs). Luciferase reporter gene experiments confirmed that there was a target relationship between lncSNHG8 and miR-224-3p. In conclusion, lncSNHG8 had high diagnostic value for AS. It promoted the proliferation and migration of VSMCs by adsorption and inhibition of miR-224-3p.